Health benefit of bioactive substances in cow’s milk - Terezija Silvija Marenjak; Nina Poljičak-Milas; Ivančica Delaš (Mljekarstvo)
The very first and an essential food provided to offspring of all mammals is milk. The importance of milk and dairy products in human diet, as promoters of good health, is still investigated. Since milk's composition is rather complex, its constituents have been for many years on the priority list of research, with their positive and negative effects on human health. Milk is composed of various substances with bioactive properties and therefore milk was given an epithet of functional food. The high diversity in chemical structure enables milk constituents to support particular physiological functions of organism, and express curing effects which is scientifically proven. The scientists and researchers are still discussing possible influencesof particular bioactive components from cow’s milk on human well being, and their assessments are very often controversial. In this paper the presently known bioactive substances in cow’s milk and theirs potential implications on human health are reported, pointing the directions for further research, particularly related to increase of the most useful and the most effective milk components for the prevention of pathological processes and disease development.